Endapan Batuan Volkanik Berdasarkan Data Sistem Informasi Geografi (SIG) Daerah Danau Ranau, Propinsi Sumatera Selatan - Idarwati Idarwati (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2015)
Ranau Lake as the second biggest lake in Sumatra Island. On Plio-Pleistocene Ranau Volcano(Volcano-tectonic) eruption resulted the formation of Ranau Lake. After the great eruption of RanauVolcano, grow up another volcanoes like Seminung Volcano, and become a Ranau Volcanic Complex.At the foot of Seminung Volcano often showed sulfur gas burst activity which are indicated by thedeath of organism in Ranau Lake. The increasing of burst gas and locally earthquacke to be theprinciple one to predict the possibility of volcano eruption for anticipation and decrease the impact ofvolcano eruption. The research objective was to determain the characteristics of rocks formationsurrounding Ranau Lake using Landsat Imagery.